Urgensi Bahan Ajar Berbasis Multimedia Bagi Guru Pendidikan Agama Islam - Nur Kholis; Diana Tofan Fatchana (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2017)
As the main actor in the education process, teachers are required to develop the full potential of students: knowledge, skills, attitudes, characters and morality. The quality instructional materials that teachers use in their classroom greatly affect students’ knowledge acquisition and their skill development. The existing and easily accessable instructional materials could widen teachers’ horizon. However, misperception and misunderstanding could occur among students if the learning materials are not properly selected and taught. Ideally, teachers should develop creative, innovative, interesting, and effective instructional materials for use in their classroom. The multimedia besed instructional materials can and should be developed and used by teachers of Islamic education in school. This paper aims at discussing the development of instructional materials in general; the relationship between teachers and instructional materials; and the importance of designing teahchers’ made instructional materials using multimedia for Islamic education. It is argued here that Islamic teachers need to develop multimedia based learning materials so that their teaching will be more interesting, joyful, and effective.